2018
DOI: 10.1111/dom.13307
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone applications and self‐management of diabetes: A systematic review with meta‐analysis, meta‐regression of 21 randomized trials and GRADE

Abstract: We conducted a systematic review with meta-analysis of randomized controlled trials that evaluated the effect of diabetes mobile phone applications. A total of 1550 participants from 21 studies were included. For type 1 diabetes, a significant 0.49% reduction in HbA1c was seen (95% CI, 0.04-0.94; I = 84%), with unexplained heterogeneity and a low GRADE of evidence. For type 2 diabetes, using diabetes apps was associated with a mean reduction of 0.57% (95% CI, 0.32-0.82; I = 77%). The results had severe heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 16 publications
5
104
1
3
Order By: Relevance
“…Research indicates that the use of smartphone technologies and mobile phone applications, such as mobile health (m-health), may facilitate diabetes self-management [12]. This is due to m-health being an interactive, inexpensive and dynamic means of supporting diabetes patients with self-care behaviours [13]. Thereby reducing mortality rates by delivering effective interventions to patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that the use of smartphone technologies and mobile phone applications, such as mobile health (m-health), may facilitate diabetes self-management [12]. This is due to m-health being an interactive, inexpensive and dynamic means of supporting diabetes patients with self-care behaviours [13]. Thereby reducing mortality rates by delivering effective interventions to patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the type 2 diabetes population, low-frequency feedback (i.e., as needed or once monthly) was associated with an A1C reduction of 0.33% (−0.59 to −0.07%, I 2 = 47%), whereas high-frequency feedback (i.e., more than once per month) was associated with an A1C reduction of 1.12% (−1.32 to −0.91%, I 2 = 0). 12 The authors did not identify a potential cause for this phenomenon, although a separate study found similar results. 13 Two possibilities for this difference in impact between diabetes types are 1) the small sample size in the studies investigating health professional feedback in type 1 diabetes, and 2) the different types of challenges faced daily by individuals living with type 1 and type 2 diabetes.…”
Section: A Patient With Type 2 Diabetes Is Started On Insulin Glarginementioning
confidence: 93%
“…A common feature of a diabetes app is self-monitoring of blood glucose levels, blood pressure, physical activity, weight, medication intake and food intake [ 3 , 5 7 ]. For blood glucose, blood pressure and physical activity (step counter), automatic data entry is often possible, but apps facilitating these features are likely to be associated with higher costs.…”
Section: Introductionmentioning
confidence: 99%
“…For blood glucose, blood pressure and physical activity (step counter), automatic data entry is often possible, but apps facilitating these features are likely to be associated with higher costs. Another common feature is interactive communication with health care providers [ 3 , 7 ]. Many of the apps that have been investigated showed to be effective [ 6 – 8 ]: HbA1c decreased [ 7 , 9 , 10 ] and self-management improved [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation